New Triassic Aviculopectinoidea (Bivalvia), with notes on the taxonomic concept of the superfamily. (March 2021) - Hautmann, Michael; Friesenbichler, Evelyn; Grădinaru, Eugen; Jattiot, Romain; Bucher, Hugo
Abstract: We describe two new genera of Triassic Aviculopectinoidea: Cristaflabellum n. gen., which is biconvex and has a strongly plicate shell, and Globodiscus n. gen., which is equiconvex and externally smooth or nearly so. Globodiscus contains the new species G . kiliani n. gen. n. sp. and G . vinzenti n. gen. n. sp. In order to make the taxonomic concept of the superfamily Aviculopectinoidea more consistent with that of its sister group Pectinoidea (scallops), we use tribes rather than families or subfamilies for accommodating the new taxa. Cristaflabellum is placed in the tribe Antijanirini (previously family Antijaniridae), whereas Globodiscus is made the type genus of the new tribe Globodiscini. Both tribes are placed within the family Aviculopectinidae, which is revised to include both equiconvex and inequiconvex taxa. We suggest that tribes are a more appropriate taxonomic rank for many of the previously erected species-poor families and subfamilies of Aviculopectinoidea. UUID: http://zoobank.org/d143663a-9016-459f-8e24-660102adcf6a